DIGITAL TRANSFORMATION AND SUSTAINABILITY: IS PEER-TO-PEER LENDING A SOLUTION? - Yen Efawati; Rinawati Rinawati (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2026)
In emerging economies, understanding the interplay between digital transformation, peer-to-peer lending (P2P), and financial capability in shaping the sustainability of micro and small enterprises (MSEs) remains limited. This study examines how digital transformation influences business sustainability through a moderated-mediation model, with P2P lending as the mediator and financial literacy as the moderator. Drawing on the Resource-Based View (RBV) and the knowledge-based view, digital transformation is seen as a strategic intangible capability that enables firms to adapt and innovate. Using a quantitative approach, data were collected from 385 MSE owners in the greater Bandung area and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that digital transformation significantly enhances both P2P lending adoption and business sustainability. However, P2P lending, both directly and indirectly, does not contribute to sustainability unless supported by high financial literacy. In addition, financial literacy strengthens the indirect effect of digital transformation through P2P lending. Theoretically, this study integrates RBV and fintech perspectives within a moderated mediation framework. In practice, it highlights the need for MSEs to align digital adoption with financial capability development to ensure that fintech lending effectively contributes to long-term sustainability.